Pengembangan Aplikasi Penjualan Peralatan Industri Berbasis Web Studi Kasus: Sembada Anugrah Teknik - Edo Hardianto ButarButar (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop an e-commerce application to sell and buy online. This e-commerce application provides an alternative for users who buy goods via the Web. The software design method used in this research is the Rational Unified Process (RUP) and software analysis modeling using the Unified Modeling Language (UML). The appearance of the application is designed with the PHP programming language. Laravel functions as an API controller that connects the framework to the database and uses the PHP MySQL database structure. The results of this study are e-commerce applications for selling and buying goods.